Тактичні та організаційні особливості зняття інформації з транспортних телекомунікаційних мереж - Щербаковський, М. Г.; Shcherbakovskyi, M. H.; Коршенко, В. А.; Korshenko, V. A.; Михайло Щербаковський (Криміналістика і судова експертиза: міжвідом. наук.-метод. зб., присвяч. 105-річчю заснування судової експертизи в Україні. – Київ, 2018. – Вип. 63, ч. 1. – С. 154-162, 2018)
Зняття інформації із транспортних телекомунікаційних мереж – складна негласна слідча (розшукова) дія, що складається з сукупності пошуковопізнавальних, технічних та посвідчувальних прийомів, в якій важливе значення має тактичний аспект. Слідчий послідовно вирішує ряд тактичних завдань: встановлює ідентифікаційні ознаки особи або обладнання, визначає виконавців, попередньо знайомиться із отриманою інформацією і відбирає важливу для розслідування, за необхідності залучає спеціалістів, оцінює результати слідчої дії. Отримані носії інформації можуть бути піддані судово-експертному дослідженню для отримання нових доказів.

The extraction of information from backhaul telecommunications networks is one of the most effective ways of obtaining information exchanged by persons related to a crime. This silent investigative (search) action in which it is possible to single out procedural, organizational, tactical and technical aspects consists of a combination of search and cognitive, technical and certifying techniques. There are several typical investigative situations that cause the need to extract information from backhaul telecommunication networks: the suspect can contact his accomplices, other persons; the victim can receive messages from the criminal; unauthorized interference in victim computer is possible; the wanted suspect can contact with a certain persons (relatives, acquaintances, accomplices in the crime); the phone number, e-mail or other parameters of the addressee are known, but the person using the communication channel is unidentified. To conduct an investigative action, it is necessary to identify the observation subscriber, the backhaul telecommunications network, the final equipment, on which interference into private communication can be effected. An effective technique is the investigator's ability to periodically get acquainted with the information received during the period of validity of the permission to conduct silent investigative (search) actions. This allows to obtain guidance information that helps to take measures immediately to counter a crime committed or preparing, to conduct other vowel or silent investigative (search) actions. In certain cases, during the examination of information, it is advisable to involve a specialist in the field, the content of which is accessible only to informed persons. The information was extract from backhaul telecommunication networks allows obtaining reliable data not only about the persons involved in the committed crime, but also about possible witnesses, victims, places of concealment means, items and documents containing information on the course of criminal actions, unrelated communications of suspects etc. After conducting the investigative action, analog and digital media can be investigated to establish other evidence using specialized knowledge in the form of forensic examination.

Снятие информации с транспортных телекоммуникационных сетей - один из самых эффективных способов получения сведений, которыми обмениваются лица, имеющие отношение к преступлению. Указанное негласное следственное (розыскное) действие в котором можно выделить процессуальный, организационный, тактический и технический аспекты состоит из совокупности поисково-познавательных, технических и удостоверяющих приемов. Существует несколько типичных следственных ситуаций, которые вызывают необходимость снятия информации с транспортных телекоммуникационных сетей: подозреваемый может связываться со своими сообщниками, другими лицами; потерпевший может получать сообщения от преступника; в работу компьютера потерпевшего возможно несанкционированное вмешательство; с определенным лицом (родственники, знакомые, соучастники преступления) может связаться подозреваемый, который находится в розыске; известны телефонный номер, электронная почта или другие параметры адресата, но лицо, пользующееся каналом связи, не установлено. Для проведения следственного действия необходимо идентифицировать абонента наблюдения, транспортную телекоммуникационную сеть, конечное оборудование, на котором может осуществляться вмешательство в частное общение. Эффективным приемом является возможность следователя периодически знакомиться с информацией, получаемой в течение срока действия разрешения на проведение негласных следственных (розыскных) действий. Это позволяет получить ориентирующую информацию, которая помогает немедленно принять меры по противодействию преступления, совершаемого или готовящегося, провести другие гласные или негласные следственные (розыскные) действия. В определенных случаях в ходе исследования информации целесообразно привлечение специалиста для понимания сообщений, содержание которых доступно только осведомленным лицам. Информация снятая с транспортных телекоммуникационных сетей, позволяет получить достоверные данные не только о лицах, причастных к совершенному преступлению, но и о возможных свидетелях, потерпевших, о местах сокрытия орудий, предметов и документов, содержащих информацию о ходе преступных действий, неустановленные связи подозреваемых лиц и т.п. После проведения следственного действия аналоговые и цифровые носители информации могут быть исследованы для установления других доказательных фактов с использованием специальных знаний в форме судебной экспертизы.
Тактические и организационные особенности снятия информации с транспортных телекоммуникационных сетей
Tactical and organizational features of information extraction from backhaul telecommunication networks
Keywords: телекомунікаційні мережі; ідентифікаційні ознаки; інформація; telecommunication networks; identification features; information; телекомуникационные сети; идентификационные признаки; информация; Криміналістика. Criminalistics. Криминалистика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; зняття інформації з транспортних телекомунікаційних мереж; снятие информации с транспортных телекоммуникационных сетей; removal of information from transport telecommunication networks